Quality Strategy and its Impact on Administrative Organizations An Analytical Study of the Opinions of a Sample of Officials of the Divisions and Administrative Units in the Representative Organization of the Ministry of Education in Erbil (NTU journal for Administrative and Human Sciences (JAHS), 2025)
This study aimed to identify the quality strategy (commitment of senior management to quality, employee participation) and its impact on administrative organizations, from the point of view of divisional and unit officials in the representative organization of the Ministry of Education in Erbil. A special, precise questionnaire form was used by the researchers to achieve the objectives of the study. It was distributed to all members of the sample included in the study, and their number reached (28) division and unit officials. In order to answer the study’s questions and hypotheses, the researchers extracted the arithmetic means, standard deviations, and multiple regression equation by relying on the statistical program (SPSS). Based on the above, the study found a statistically significant effect at the significance level (a?0.05) for senior management’s commitment to quality and employees’ participation in administrative organizations. The study came out with a number of conclusions, including: that there is a statistically significant impact of the quality strategy on administrative organizations at a general rate of (69.6%). The study concluded with a set of recommendations, the most important of which were: the necessity of spreading the culture and improving the quality strategy among the employees of the Ministry of Education Representative Organization in Erbil and introducing them to its foundations and principles and its effects on developing administrative organizations and its importance in achieving the organization’s goals.